Evaluation of Concordance between Hip and Spine T Scores in the Diagnosis of Osteoporosis in Men Over Age of Fifty - Oya Özdemir; Sina Yasrebi; Yeşim Gökçe Kutsal (Türk Osteoporoz Dergisi)
Objective: The aim of this study was to evaluate the concordance in diagnosis of osteoporosis based on the World Health Organization (WHO) classification of bone mineral density (BMD) measurements of hip and spine in men aged ≥50 years. Materials and Methods: The BMD measurements, which were measured via dual x-ray energy absorptiometry (DXA), of 10.049 patients admitted to our hospital between January 1, 2012 and August 1, 2013 were retrospectively reviewed and 649 men aged ≥50 years were included in the study. It was defined as minor discordance when the difference between two sites was no more than one WHO diagnostic class. Major discordance was present when one site is osteoporotic and the other is normal. Results: The mean age of the participants was 68.7±9.1 (50-93) years. The mean values of lumbar spine and total hip BMD values were 1.1681±0.231 (0.629-2.267) g/cm2 and 0.933±0.152 (0.414-1.444) g/cm2, respectively. According to L1-L4 vertebra T score, 54.4% of the individuals were classified as normal, 33% were osteopenic, and 12.6% were osteoporotic. Whereas, according to total femur T score 41.7% of participants were normal, 47.5% had osteopenia, and 10.8% had osteoporosis. Concordance of T scores, minor discordance, and major discordance were seen in 59.6%, 37.6%, and 2.8% of the patients, respectively. Conclusion: In this study, it was shown that in 4 of every 10 male patients aged ≥50 years tested by DXA, T score discordance between spine and total hip measurement sites is present. This ratio is similar to the results of previous studies investigating the prevalence of this phenomenon in larger samples including both postmenopausal women and men. Clinicians should keep in their mind that T score discordance is a prevalent finding and can be related to various physiological and pathological patient factors as well as the performance or analysis of DXA itself.